Continuous‐Infusion Topotecan and Erlotinib: A Study in Topotecan‐Pretreated Ovarian Cancer Assessing Shed Collagen Epitopes as a Marker of Invasiveness. (21st February 2014) - Warner, Eiran; Liebes, Leonard; Levinson, Benjamin; Downey, Andrea; Tiersten, Amy; Muggia, Franco
Abstract: Background: Continuous‐infusion topotecan with erlotinib has the potential to reverse topotecan resistance due to drug efflux mechanisms. We assessed the activity of such a regimen in ovarian cancer patients previously failing bolus topotecan. Assay for shed collagen epitopes recognized by antibody HU177 during treatment explored its ability to reflect tumor invasion. Methods: Topotecan 0.4 mg/m 2 per day was administered by continuous infusion for 9–10 days every 3 weeks. Erlotinib, 150 mg orally, was administered on days 1–10 of each cycle. Cycles were repeated until progression or toxicity. Serum for shed HU177 collagen epitopes was collected weekly. This was a two‐stage design to detect a CA‐125 response rate of at least 20% in 30 patients after completing two treatment cycles. The trial would be terminated early if there were less than two CA‐125 responses in 16 patients. Four or more CA‐125 responses in 30 patients would justify further study of this regimen in prior topotecan treatment failures. Results: Six patients were enrolled, with four receiving three or more cycles and one achieving a partial response by cancer antigen 125 (CA‐125) criteria. Shed epitope levels became undetectable on at least one measurement in all patients who received three or more cycles (Fig. 1A ) and reappeared concomitantly with rises in CA‐125 and clinical progression (Fig. 1B ). After logistical delays, the trial was closed by the sponsor's decision to stop developing erlotinib in ovarian cancer. Conclusion: Continuous‐infusion topotecan with erlotinib was found safe in six pretreated ovarian cancer patients; one met CA‐125 criteria for partial response. Serial shed epitope levels to reflect invasiveness deserve further study. Abstract : 摘要 背景 . 连续输注托泊替康联合厄洛替尼有望因药物释放机制而逆转托泊替康耐药。我们在既往托泊替康推注治疗失败的卵巢癌患者中评估了该方案的作用。治疗期间使用HU177抗体识别shed胶原蛋白抗原表位，并探索通过这种检测来观察肿瘤浸润情况的能力。 方法 . 托泊替康0.4 mg/m 2 每日输注，连续9 ∼ 10天，每3周1次。厄洛替尼150 mg口服，每个治疗周期第1∼10天给药。疗程重复，直至疾病进展或出现毒性反应。每周收集1次血清shed HU177胶原蛋白抗原表位。研究为2阶段设计，在至少20%的完成2个治疗周期的30例患者中检测癌症抗原（CA）‐125应答率。如果16例患者中出现CA‐125应答者少于2例，则提前结束试验。30例患者中若出现≥ 4例CA‐125应答，将证明有必要进一步在前期托泊替康治疗失败的患者中研究该方案。 结果 . 入组6例患者，其中4例接受了≥3个周期治疗，1例达到CA‐125部分缓解标准。接受了≥ 3个周期治疗的全部患者中，Shed抗原表位水平在至少1次测量中不可检出（图1A），当CA‐125升高和临床进展时则同期再次出现（图1B）。由于后勤延误，赞助商决定结束试验，且不继续在卵巢癌患者中开展厄洛替尼研究。 结论 . 连续输注托泊替康联合厄洛替尼在6例既往接受过治疗的卵巢癌患者中是安全的；1例达到CA‐125部分缓解标准。需要进一步研究来观察可否通过连续shed抗原表位水平来反应肿瘤浸润。 The Oncologist 2014;19:250